2016
DOI: 10.2807/1560-7917.es.2016.21.30.30301
|View full text |Cite
|
Sign up to set email alerts
|

Influenza epidemiology, vaccine coverage and vaccine effectiveness in children admitted to sentinel Australian hospitals in 2014: the Influenza Complications Alert Network (FluCAN)

Abstract: The Influenza Complications Alert Network (FluCAN) is a sentinel hospital-based surveillance programme operating in all states and territories in Australia. We summarise the epidemiology of children hospitalised with laboratory-confirmed influenza in 2014 and reports on the effectiveness of inactivated trivalent inactivated vaccine (TIV) in children. In this observational study, cases were defined as children admitted with acute respiratory illness (ARI) with influenza confirmed by PCR. Controls were hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 20 publications
4
40
0
Order By: Relevance
“…However, our conclusions are limited by the efficacy of the vaccines available for each disease. The estimated effectiveness of influenza vaccine in prevention of hospitalised influenza was 55.5% in a recent Australian study . Vaccine effectiveness against death was 65% (95% CI 54–74%) among children aged 6 months to 17 years in a recent US study, and 51% (95% CI 31–67%) in a subgroup of children with high‐risk conditions .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, our conclusions are limited by the efficacy of the vaccines available for each disease. The estimated effectiveness of influenza vaccine in prevention of hospitalised influenza was 55.5% in a recent Australian study . Vaccine effectiveness against death was 65% (95% CI 54–74%) among children aged 6 months to 17 years in a recent US study, and 51% (95% CI 31–67%) in a subgroup of children with high‐risk conditions .…”
Section: Discussionmentioning
confidence: 97%
“…Previously healthy young children with influenza have been shown to have high hospital admission rates and may be more likely to die before hospital admission or within 3 days of symptom onset, compared to those with underlying medical conditions . While influenza vaccination is recommended in Australia for all children between 6 months and 5 years of age, it is only funded under the NIP for those at higher risk and coverage is very low . Coverage recorded in ACIR was less than 2.5% in children aged 6 months to less than 5 years of age between 2005 and 2014 (excluding Western Australia, where a funded seasonal influenza immunisation programme for children commenced in 2008) .…”
Section: Discussionmentioning
confidence: 99%
“…In an investigation, Kuster et al reported incidence rates of influenza in vaccinated and unvaccinated HCWs were 6.5% and 18.7%, respectively . Children have the highest rate of influenza infection which led to hospitalization . The prevalence of influenza in children was reported 9.7%–29.0% based on the region by US influenza Surveillance Report .…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of influenza among Australian hospitals reported by Blyth et al They detected influenza A in 90% of 402 patients. Among the positive samples, H1N1, pdm09 and H3N2 were confirmed as a most frequent subtype . Epidemiological studies can be used for several purposes such as identify the dominant types of the virus to vaccination strategies for population and subgroups, identify high‐risk groups and identification of the epidemiological pattern of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation